Performance on the initiatives taken toward financial sustainability of public universities in Malaysia - Kadir M.R.A.; Cotter C.D. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The initiative to reduce Public Universities (PUs) dependency on the Malaysian federal government grants for operation and development expenditure was highlighted in the Malaysian Education Blueprint (MEB) 2015-2025. In the MEB, PUs are expected to strengthen their income generation to achieve financial sustainability while staying focus on their core educational missions. The purpose of this study is to assess income enhancement initiatives carried out by PUs to achieve financial sustainability. The initiatives suggested in UniTP Purple Book to help PUs in their quest to be financially sustainable is used as the variables. This study found that the PUs in Malaysia have a clear objective towards achieving financial sustainability. However, their initiatives in enhancing income are limited, mostly on the routine tasks and activities with low financial risks. BEIESP.